DRUG RELEASE PROFILE OF MALIC ACID-PHTHALIC ACID BUTANE 1,4-DIOL COPOLYESTER (Biological Sciences - PJSIR, 2004)
Five copolyesters (I-V) in varying mole ratios of malic acid and phthalic acid were separately synthesized with 1 mole of butane 1,4-diol using p-toluene sulfonic acid (0.4% of the total weight) as catalyst under vacuum at 120-125°C for about 6 h . The malic acid-phthalic acid-butane 1,4-diol copolyesters (MPBC) were characterized by their IR spectra, molecular weight, elemental analysis and solubility behavior in common organic solvents. The polymer III had the highest molecular weight and it was selected for subsequent experiments. Its hydrolytic degradation study in solutions of different pH values showed that it remained intact in solutions of pH values 1.2-6.0, but gradually degraded in solutions of pH values >6.0. Drug delivery profile of MPBC as an enteric coating material was investigated in simulated gastric fluid (pH 1.2) and then in simulated intestinal fluid (pH 7.4), it was found that the drug release pattern did not conform to enteric coating requirements. In the case of matrix tablets where drug was dispersed in the MPBC, it was found that the drug delivery was zero order up to 12 h releasing 88.0% of diclofenac sodium and up to 13 h releasing 86.50% of naproxen, afterwards release of drugs was negligible.